2020
DOI: 10.1101/2020.01.09.901108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic diversity and activity screening of cultivable actinobacteria isolated from marine sponges and associated environments from the western coast of India

Abstract: 25Phylogenetic diversity of cultivable actinobacteria isolated from sponges and associated 26 environments of intertidal zones, along the northern parts of west coast of India, were studied 27 using 16S rRNA gene sequences. A subset of actinobacteria were screened for three activities, 28 namely predatory behavior, antibacterial activity and enzyme inhibition. We recovered 207 29 isolates of actinobacteria belonging to 16 families and 25 genera, which could be attributed to 30 55 putative species using Poisson… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…The relative abundance of each phylum varies substantially where phylum Actinobacteria was the most abundant followed by Firmicutes, Proteobacteria and an insignificant amount of Bacteroidetes. In agreement with our report, a high abundance of phylum Actinobacteria has been found previously [ 32 , 68 , 69 ]. However, some studies have also reported a low level of the phylum Actinobacteria compared to Proteobacteria [ 64 , 66 , 67 , 70 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The relative abundance of each phylum varies substantially where phylum Actinobacteria was the most abundant followed by Firmicutes, Proteobacteria and an insignificant amount of Bacteroidetes. In agreement with our report, a high abundance of phylum Actinobacteria has been found previously [ 32 , 68 , 69 ]. However, some studies have also reported a low level of the phylum Actinobacteria compared to Proteobacteria [ 64 , 66 , 67 , 70 ].…”
Section: Discussionsupporting
confidence: 94%
“…Many of the genera reported in this study have been described as having antimicrobial activities. In addition to Streptomyces , antimicrobial activity has also been attributed to Bacillus [ 27 , 30 , 32 , 60 , 62 , 64 , 66 , 67 , 69 , 72 ], Micrococcus [ 71 , 72 , 74 ], Microbacterium [ 73 ], Gordonia [ 72 ], Sulfitobacter [ 32 ], and Kocuria [ 35 ]. Antimicrobial activities due to Fictibacillus and Limimaricola were not reported, though phylogenetically, the genus Fictibacillus is highly related to Bacillus and Limimaricola with Sulfitobacter .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Proteobacteria, several studies demonstrated the great biotechnological potential of Actinobacteria, especially those belonging to the Streptomyces genus. In fact, several bioactive compounds with antimicrobial, antiviral, antiparasitic, antiprotozoal and antitumor effects have been described [ 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Moreover, genomic analyses revealed some BGCs encoding for secondary metabolites, such as PKS I and III, NRPS (nonribosomal peptides), terpene and bacteriocin gene clusters from a sponge-derived Actinobacteria showing antimicrobial activities [ 108 , 109 , 110 , 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…Actinomycetes usually exist in mixed bacterial consortium in soil, water, marine sediments, and sponges [47,48]. For the sake of eliminating non-sporulating bacteria from samples, each sample is usually subjected to pre-heat treatment at 60 • C for 15 min.…”
Section: Isolation and Maintenance Of Cultivable Actinobacteria For Bmentioning
confidence: 99%